The Effect of NaHCO3 and Mg2+ Addition in Haematococcus pluvialis Cultivation by Carbon Injection Method - W. Widayat; Annisa Metantya Maharani; Siti Nur Khairunisa Aroli; Muhammad Hilmazar Hawari (Journal of Bioresources and Environmental Sciences, 2022)
The emission of carbon dioxide has been continuously rising year by year. Many efforts that have been used with aim of climate recovery, such as capturing CO2 with the Carbon Capture Storage (CCS) method, which is the CCS technology is one of the effective tactics for reducing carbon emissions by utilizing energy from biomass of microalgae. This research will discuss about carbon capture using microalgae Haematococcus pluvialis in a lab scale photobioreactor (PBR), and resulting the optimum biomass productivity for Haematococcus pluvialis has occurred in the H2 variable (50 ppm Mg2+). This happens because of addition of Mg ions above 50 ppm can decrease the yield of biomass productivity, since Haematococcus pluvialis cannot live in high salinity concentrations. Further research should make a calculation of optimal cost incurred at the optimal carbon concentration that can be captured by microalgae, also the results of increasing value of the microalgae biomass produced for the comprehensive use of the microalgae.